TESTING OF PRODUCTION MATERIAL FABRICS IN THE GARMENT INDUSTRY BY THE QC DEPARTMENT TO MAINTAIN QUALITY - Tripratama B, Reza; Basuki, Puji; Wahyu S, Candra; Dyah P, Shintawati; Agustin, Niyar Candra (Universitas Islam Nahdlatul Ulama Jepara, 2025)
Quality inspection of materials before entering the production stage was essential to ensure product quality and optimize resource efficiency. This study aimed to map the quality control procedures implemented by garment industries and evaluate the effectiveness of these procedures in reducing the occurrence of production failures (rejects) that had already passed through lengthy production processes. Such failures resulted in significant and costly waste. A case study was conducted in a garment manufacturing company using observation, interviews, and documentation as data collection methods. The results showed that in order to produce high-quality garments, fabric as the primary raw material must undergo several inspection steps, including weighing, measuring length and width dimensions, testing fiber strength, evaluating colorfastness, and completing an inspection report form as proof of examination. In addition to inspections upon material arrival, in-process quality control was also performed by measuring each part of the garment. These measurements had to follow the same method used by the production department to avoid discrepancies in interpretation when determining whether a product met specifications (accepted) or should be rejected (reject). PENGUJIAN KAIN BAHAN PRODUKSI PADA INDUSTRI GARMEN OLEH BAGIAN QC UNTUK MENJAGA MUTUPengujian kualitas bahan sebelum masuk ke tahapan proses produksi sangat penting dalam menjaga mutu dan efisiensi sumber daya yang digunakan. Tujuan penelitian ini adalah untuk memetakan apa saja yang dilakukan oleh industri garmen untuk melihat seberapa efektif tahapan pengujian yang dilakukan apakah mampu mengurangi kegagalan produksi (reject) yang terlanjur melewati tahapan produksi yang panjang. Jika ini terjadi merupakan pemborosan yang sangat merugikan. Metode yang dilakukan adalah melakukan studi kasus pada industri garmen dengan diawali observasi, wawancara dan dokumentasi. Hasil yang diperoleh adalah untuk mendapatkan hasil pakaian berkualitas diperlukan langkah pengujian kain sebagai bahan baku dengan cara pengecekan berat dengan cara ditimbang, pengukuran dimensi panjang & lebar, pengujian kekuatan serat, pengujian warna, dan pengisian formulir inspection report sebagai bukti pemeriksaan. Selain ketika kedatangan ada juga pemeriksaan mutu ketika dalam proses pengerjaan dengan cara pengukuran tiap bagian baju dengan syarat metode tersebut harus sama dengan yang dilakukan oleh bagian produksi. Hal ini untuk menjaga terjadinya perbedaan persepsi pada saat menentukan hasil pengukuran antara sesuai spesifikasi (accepted) atau reject.